Feasibility Study on the Development of Asia Padang Clinic - Yass Andria; Seveni Santi; Yulina Eliza; Sutiyem Sutiyem (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the feasibility of developing Asia Padang Clinic in order to upgrade its status from a Primary Healthcare Facility (FKTP) to an Advanced Referral Healthcare Facility (FKTL). The feasibility assessment is conducted based on five main aspects, namely market feasibility, economic feasibility, legal feasibility, technical feasibility, and social feasibility. This study adopts a mixed-methods approach, with primary data collected through questionnaires and interviews involving 100 respondents, consisting of patients and employees of Asia Padang Clinic. Quantitative data were analyzed using multiple linear regression analysis with the assistance of IBM SPSS Statistics version 25. The results indicate that, both simultaneously and partially, all five feasibility aspects have a positive and significant effect on the decision to develop Asia Padang Clinic. These findings suggest that Asia Padang Clinic has met the feasibility criteria to be developed and upgraded from a Primary Healthcare Facility (FKTP) to an Advanced Referral Healthcare Facility (FKTL). Therefore, clinic management is advised to formulate an integrated development plan encompassing investment strengthening, compliance with facility and infrastructure standards, human resource development, service quality improvement, and adherence to healthcare regulations. The implementation of this development is expected to enhance the quality of healthcare services and the institution’s competitiveness in a sustainable manner.